YouTube as a source of information on preventing the use of valproic acid in women during pregnancy - Boyang Qu; Binbin Kang; Xingyang Chen; Yanrong Ao; Liping Wang; Weiwei Cui (BMC, 2023)
Abstract Background YouTube™ ( http://www.youtube.com ), as a very popular video site worldwide, is increasingly being used as a platform to disseminate health information. The purposes of this review were to assess the overall usefulness of the information on the prevention of valproic acid use in women during pregnancy on YouTube™ for patients. Methods The YouTube™ website was systematically using 8 keywords. One hundred and fifty four videos meet the selection criteria. The researcher evaluated the video duration, days since upload, views and the likes. These videos are categorized as Education, News & Politics and People & Blogs. We designed a usefulness scoring scheme to assess videos quality and classified them as "slightly useful", "useful" and "very useful". The Kruskal-Wallis test was used to determine whether differences existed between total usefulness scores and categories and Pearson chi-square test for categorical variables. Results The majority of videos were educational (62.8%). The "People & Blogs" and "News & Politics" videos scored significantly higher, but had no significant difference in days since upload, views, views/day or likes. More than half of the videos (91/154) were categorized as "useful". The mean posted days (p = 0.045) was significantly different in the useful group compared with the slightly useful group. There were no correlation between usefulness and the number of days since upload, duration, views, views/day, or likes. Conclusion YouTube™ is a promising source of information regarding the use of valproic acid during pregnancy. "News & Politics" videos are the most usefulness. Considering the presence of more slightly useful information, publishers need to improve more comprehensive video content that includes replacement medications, diagnoses and treatments. In the healthcare information space, consumers need to be directed to reliable video.